Kajian Kondisi Perkerasan Jalan Arteri di Kabupaten Sleman Menggunakan Cara Pavement Condition Index. - Perpustakaan UGM, i-lib ([Yogyakarta] : Biro Administrasi Kemahasiswaan UGM, 2001)
There are several links of arterial roads in the Sleman District of the Province of Special Teritory of Yogyakarta conecting the City of Yogyakarta with other inter provincial cities. The roads should be managed effectively and efficiently, so that it is important to evaluate the pavement condition using proper method. This research is conducted to evaluate pavement condition of the arterial roads in the Sleman District, using the Pavement Condition Index for Asphaltic Concrete Roads. Aim of the research is to determine the pavement condition of the arterial roads. The research result could be used by authority body for its pavement management. The research results show that in general the pavement condition of the arterial roads under the research is good, moreover above good. Two small areas on the Ring Road fall in fair condition, and the suggested method to rehabilitate these area is also presented.